2021
DOI: 10.1111/ijfs.15445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold‐pressing conditions on physicochemical and functional properties of cold‐pressed tigernut oil and starch isolated from press‐cake

Abstract: Tigernut tuber is a peculiar source of oil because it has high amounts of starch. To collect tigernut oil and obtain high-quality starch from pressed cake, a comprehensive validation of the cold-pressing method was conducted. At 40-60 MPa, from one pressing, 67.18-73.97% of total oil content can be obtained; with three pressings, 77.38-82.34% of total oil can be obtained. Starch yields from solvent extraction of cold-pressed press-cake are significantly higher (P < 0.05) compared with native tigernut flour. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
(53 reference statements)
2
15
0
Order By: Relevance
“…The proximate composition of moisture of samples SP8, SP16, SP24, SP32, and SP40 was determined using method reported by Miao et al . (2021). In brief, samples (4.00 g) were placed in glass containers and then dried in an oven (DHG‐9140A; Shanghai, China) at 103 °C for approximately 80 min until a stable weight was reached.…”
Section: Methodsmentioning
confidence: 99%
“…The proximate composition of moisture of samples SP8, SP16, SP24, SP32, and SP40 was determined using method reported by Miao et al . (2021). In brief, samples (4.00 g) were placed in glass containers and then dried in an oven (DHG‐9140A; Shanghai, China) at 103 °C for approximately 80 min until a stable weight was reached.…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al 29 found that the TNS isolated from the cake after cold press extraction exhibited the highest water absorption capacity. Miao et al 31 reported that starch yield from alkali extraction of cold-pressed press-cake was 15.99%, which was significantly higher compared with that of native tiger nut flour (11.74%).…”
Section: Extraction Of Tiger Nut Starchmentioning
confidence: 99%
“…To meet the demands of the food industry for largescale continuous production, frozen dough is widely used for wheat flour-based product processing, such as steamed stuffed bun, dumplings, bread, and biscuits, due to its long shelf life and ease of processing (Li et al, 2022). The global frozen dough market was reported to be worth USD 18.59 billion in 2020 and is predicted to reach a value of USD 27.44 billion by the end of 2025 (Ahmed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tigernut ( Cyperus esculentus L.) is known by an assortment of names, i.e ., chufa, yellow nutsedge, or earth almonds. Due to its extreme resistance to drought, flooding, and pests and its ease of cultivation, it is now widely planted in extratropical, subtropical, and tropical regions (Miao et al ., 2022). The oil content (30–35%) of tigernut is much higher than that of traditional oilseed crops such as soybean, rapeseed, and peanut (Cai et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%